Active commuting and cardiovascular disease risk: The CARDIA study - Gordon-Larsen, Penny (2009)
BACKGROUND: There is little research on the association of lifestyle exercise, such as active commuting (walking or biking to work) with obesity, fitness, and cardiovascular disease (CVD) risk factors. METHODS: This cross-sectional study included 2,364 participants who worked outside the home from 2005–06 of the CARDIA study. Associations between walking/biking to work (self-reported time, distance, and mode of commuting) with: body weight (measured height and weight); obesity (BMI≥30 kg/m(2)); fitness (symptom-limited exercise stress testing); objective moderate-vigorous physical activity (accelerometry); and CVD risk factors [blood pressure (oscillometric systolic and diastolic); and serum measures (fasting measures of lipids, glucose, and insulin)] were separately assessed by sex-stratified multivariable linear (or logistic) regression modeling. RESULTS: 16.7% of participants used any means of active commuting to work. Controlling for age, race, income, education, smoking, exam center, and physical activity index excluding walking, men with any active commuting (versus none) had reduced likelihood of obesity (OR=0.50; 95% CI 0.33, 0.76), reduced CVD risk: ratio of geometric mean triglycerides: 0.88 (0.80, 0.98); ratio of geometric mean fasting insulin: 0.86 (0.78, 0.93); difference in mean diastolic blood pressure (mmHg):−1.67; −3.20, −0.15)], and higher fitness; mean difference in treadmill test duration {seconds}: 50.0 (31.5, 68.6) in men and 28.8 (11.6, 45.9) in women. CONCLUSIONS: Active commuting was positively associated with fitness in men and women and inversely associated with body mass, obesity, triglycerides, blood pressure and insulin in men. Active commuting should be investigated as a modality for maintaining or improving health.